STRATEGI PENUMBUHAN PERAN GAPOKTAN DALAM PEMASARAN KELAPA DALAM DI KABUPATEN TANJUNG JABUNG TIMUR - Sovia Maryanti, Endang; Napitupulu, Dompak; Ningsih, Rozaina (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2021)
Coconut plant is one of the commodities that has high economic value because it has value as a multipurpose crop. Deep coconut is one of the seven leading plantation commodities in Jambi Province and ranks third after rubber and palm oil. In the life of the farmer community, the position and function of the farmer institution in this case farmer group union is a part of social institutions that facilitate social interaction or social interplay within a community. This farmer institution also has a strategic point (entry point) in driving the agribusiness system in the countryside The purpose of this study is to analyze the role of Gapoktan in marketing coconut commodities in and analyze the strategy to grow the role of Gapoktan in marketing coconut in the East TanjungJabung Regency. This research uses primary and secondary data sources. Secondary data recorded systematically was obtained by observation and interview. Determination of the sample using a random sampling method with a total sample of respondents of 30 respondents. The data obtained were analyzed using descriptive analysis methods and SWOT analysis (Strengths, Weaknesses, Oppurtunities and Threats). The conclusions of the results of this study are (1) In general, East TanjungJabung Regency has the potential to develop coconut commodities in terms of geographical and climate aspects that are very supportive. Gapoktan as a marketing unit has not functioned as it should, so the attachment of Gapoktan to middlemen is still high; (2) The position of the Gapoktan role lies in awareness I and the strategy that can be applied in this position is to support the policy of growing the role of an aggressive Gapoktan (growth oriented strategy) or aggressive strategy (aggressive strategy). The strategies adopted are (a) cooperating with investors as partners in processing coconut, (b) optimizing empowerment, training and increasing the Gapoktan function as a marketing unit, (c) issuing regulations on land use regulations for deep coconut plants, (d) optimizing Gapoktan member resources (e) to grow cooperatives as a marketing agenda for coconut.